A retrospective review of treatment patterns of antiemetic agents for chemotherapy-induced nausea and vomiting. (25th April 2018) - Alamri, Abdulrahman; Alawlah, Yousef A; Qiao, Yanru; Wang, Junling
Objectives: To evaluate the treatment pattern of antiemetic agents used for chemotherapy-induced nausea and vomiting in a tertiary hospital in Saudi Arabia. Methods: Over a period of 7 weeks, all new chemotherapy order sheets were collected and evaluated for chemotherapy-induced nausea and vomiting management. We compared each antiemetic regimen used for chemotherapy-induced nausea and vomiting prophylaxis with three international antiemetic guidelines by the following organizations: the Multinational Association of Supportive Care in Cancer, the American Society of Clinical Oncology, and the National Comprehensive Cancer Network for the clinician. Results: A total of 152 cancer patients were included in the study, for whom 289 chemotherapy physician orders included antiemetic regimens. Approximately 17.3% of the chemotherapy protocols had total minimal emetogenicity risk, 22.5% had low risk, 37.02% had moderate risk, and 23.18% had high risk. For acute emesis, 27.57% of the antiemetic regimens followed at least one of the three reference guidelines. For delayed emesis, only 20.16% of the antiemetic regimens adhered to at least one of the three reference guidelines. Conclusion: Adherence to treatment recommendations and antiemetics prescribing for chemotherapy-induced nausea and vomiting was suboptimal at this hospital. However, institutional antiemetic guidelines and oncology pharmacists could play an important role in better assessment and management of chemotherapy-induced nausea and vomiting.